Comparison of Tranexamic Acid Versus Calcium Dobesilate (Doxium) for Management of Dysfunctional Uterine Bleeding - Rehana Bibi, Safia Parveen, Asma Naeem, Habiba Noreen, Javeria Tabassum, Amna Yasmin (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Dysfunctional uterine bleeding (DUB) is a common gynecological condition characterized by abnormal uterine bleeding in the absence of structural pathology. It significantly affects the physical, psychological, and social well-being of women. Medical management remains the first-line treatment, with tranexamic acid widely used; however, calcium dobesilate (Doxium) has recently emerged as a potential alternative due to its microvascular protective effects. Objective: To compare the efficacy and safety of tranexamic acid versus calcium dobesilate in the management of dysfunctional uterine bleeding. Methods: This randomized controlled trial was conducted at the Department of Obstetrics and Gynecology, DHQ Hospital Sahiwal, over one year. A total of 100 women aged 18–40 years diagnosed with dysfunctional uterine bleeding were enrolled and randomly allocated into two groups (n=50 each). Group A received tranexamic acid 1000 mg/day, while Group B received calcium dobesilate 500 mg for 5 days during each menstrual cycle for four months. Menstrual blood loss was assessed using the pad/tampon weight method at baseline and after treatment. Efficacy and adverse effects were evaluated and analyzed using SPSS version 21, with p < 0.05 considered statistically significant. Results: The mean age of participants was 30.12±6.32 years in the tranexamic acid group and 29.12±6.72 years in the calcium dobesilate group. Calcium dobesilate demonstrated significantly higher efficacy compared to tranexamic acid (88% vs 72%, p = 0.046). Adverse effects were observed in 30% of patients receiving tranexamic acid and 38% of those receiving calcium dobesilate; however, this difference was not statistically significant (p = 0.673). Gastrointestinal disturbances were the most commonly reported side effects in both groups. Conclusion: Calcium dobesilate is more effective than tranexamic acid in the treatment of dysfunctional uterine bleeding, without significant adverse effects. It could be a good option for treatment. Keywords: Dysfunctional uterine bleeding, Tranexamic acid, Calcium dobesilate, Heavy menstrual bleeding, Randomized controlled trial.